Occult Sciences, Volume 1 The Philosophy of Magic, Prodigies and Apparent Miracles - Salverte, Eusèbe (Cambridge library collection. Spiritualism and Esoteric Knowledge, 1846)
This examination of the connection between the belief in miracles and religious practices in ancient times was originally written by French politician and polymath Anne-Joseph-Eusèbe Baconnière de Salverte (1771–1839) and published in 1829. In 1846, it was translated into English by a Scottish physician and writer, Anthony Todd Thomson (1778–1849), and published in two volumes. Thomson explains that Salverte's work was an important study of miracles and the power of priests, and he had 'performed a beneficial service in throwing open the gates of ancient sanctuaries'. However, Thomson also states that he differed from Salverte over the idea of the miraculous, and that he had expunged or heavily edited any passages relating to Christianity, even changing 'miracles' in the original subtitle to 'apparent miracles'. Volume 1 begins with a consideration of human credulity before discussing magic in the ancient world, and offering explanations for supernatural phenomena